Aplikasi Mikoriza dan Pupuk Hijau Lamtoro untuk Pertumbuhan dan Hasil Tanaman Bawang Merah (Allium ascalonicum L.) di Tanah Inceptisol - Beatrix Normauli Siagian; Armaini Armaini; Idwar Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aim of this research is to know application of mycorrhizae fungi vesikula arbuskula (CMA), lamtoro green fertilizer and its combination, and get the best dose of CMA, lamtoro and combination for the growth and production of onion crop (Allium ascalonicum L.) in Inceptisol soil. The research has been conducted at Experimental Garden of Agriculture Faculty of Riau University from October to December 2017. This research used factorial randomized block design (RAK). The first factor was the CMA of dose (0, 5, and 10 g per plant) and the second factor was the lamtoro of dose (0, 15 and 25 t.ha-1). The parameters observed was plant height, number of leaves per hill, number of tubers per hill, tuber bulbs per clump, percentage of diameter size of onion bulbs (large, medium and small), weight in the shelf, harvest age and percentage of infected root of mycorrhizae. The data obtained was analyzed statistically using variance then the results obtained were followed by Duncan's multiple-range test of 5%. The results showed that the combination of CMA and lamtoro treatments influenced the number of leaves and percentage of the largest tuber size. At a dose of CMA 10 g per plant and lamtoro 25 t.ha-1 can increase the weight in the shelf. Application of CMA at a dose of 5 g per plant tended to influenced the plant height, number of leaves, weight in the shelf. Application of lamtoro at a dose of 25 t.ha-1 tended to influencedtuber bulbs and weight in the shelf. The combination of CMA 10 g per plant and lamtoro 25 t.ha-1, CMA with a dose of 5 g per plant and lamtoro25 t.ha-1 tended to give the best results on the growth and production of onion crop. Keywords: onion, CMA, lamtoro, Inceptisol